Endovascular therapy for Angio‐sealTM‐related acute limb ischemia: Perioperative and long‐term results. (13th February 2017) - Dong, Hui; Peng, Meng; Jiang, Xiongjing; Che, Wuqiang; Zou, Yubao; Xu, Bo; Yang, Yuejin; Gao, Runlin
Abstract : Objectives: To investigate the perioperative and long‐term outcomes of endovascular therapy for Angio‐seal TM ‐related acute limb ischemia. Background: Currently, limited data are available on the optimal treatment strategy for Angio‐seal TM ‐related acute lower limb ischemia. Methods: The prospectively maintained patient database of our institution was retrospectively searched to identify all patients who developed acute lower limb ischemia after use of the Angio‐Seal TM and received endovascular treatment from January 2010 to February 2016. The clinical and follow‐up data were evaluated. Results: Thirty‐two patients with Angio‐Seal TM ‐related acute limb ischemia underwent endovascular therapy, resulting in an approximated incidence of 0.29% of all implanted devices. The overall procedural success rate was 96.9%. With regard to the patients who underwent successful endovascular treatment, the culprit lesion was located in the common femoral artery in 22 (71.0%) cases, the femoral artery bifurcation in 3 (9.7%) cases and the superficial femoral artery in 6 (19.4%) cases. Ten (31.3%) patients had thrombosis in other distal lower limb arteries ipsilateral to Angio‐seal TM use. Eighteen (58.1%) patients underwent balloon angioplasty alone, while nine (29.0%) patients underwent balloon angioplasty and thrombolysis, and four (12.9%) patients underwent stent implantation. One patient suffered from minor bleeding at the site of application of the Angio‐seal TM . During an average of 43.5 ± 22.9 months of follow‐up, three patients with symptomatic restenosis underwent a second successful balloon angioplasty and remained asymptomatic until the last follow‐up. Conclusions: Balloon angioplasty with selective thrombolysis or stent placement was safe and effective, with a low incidence of complication and restenosis. © 2017 Wiley Periodicals, Inc.